The Influence of Work Ability, Discipline, and Motivation on Employee Performance: A Study at PT. Freeport McMorent Indonesia - Muin, Muhammad Farhan; Hakim, Lukman (Jurnal Economic Resource, 2025)
Facing increasingly tight competition in the era of economic globalization requires PT. Freeport Indonesia Industri to improve work ability, work motivation and work discipline in order to improve employee performance. The problem faced is that employee performance is not optimal, so that work ability, work motivation and work discipline need to be further improved. The purpose of this study: to determine the effect of work ability on work performance at PT Freeport Indonesia to determine the effect of discipline on performance at PT Freeport Indonesia To determine the effect of motivation on employee performance at PT Freeport Indonesia to determine the effect of discipline and motivation on employee performance at PT Freeport Indonesia. There is an influence of work ability, discipline and motivation on employee performance at PT. Freeport Indonesia. There is an influence of motivation on employee performance on the influence of work ability, discipline and motivation on employee performance at PT. Freeport Indonesia There is an influence of discipline on employee performance at PT Freeport Indonesia In this study an associative approach was used. Approach and quantitative work ability, work ability Discipline and motivation have a significant effect on employee performance, meaning that the more work ability is improved, discipline will increase, then performance will increase and if the motivation given is better, performance will also increase significantly.